Self-Adjustment of First Year FIP UNP Students in Higher Education and Implications on Guidance and counseling Services: Descriptive Study of Students of the Faculty of Education, Padang State University - Sukardi, Tomi (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
This study aims to describe the adjustment of first year FIP students in the academic field, as well as the adjustment of first year FIP students in non-academic fields. This study used a quantitative method with a descriptive approach with a total sample of 300 people, the sample selection used the Proportional Random Sampling technique. The instrument used likert scale, measurement and processed using percentage analysis techniques by determining the mean value, standard deviation, and score. The research finds that the adjustment of first-year students is generally in the fairly good category (32.7%). Furthermore, adjustment in the academic field is in the fairly good category (40.3%) and adjustment in the non-academic field is in the fairly good category (41.0%).